PENGARUH MODEL PEMBELAJARAN STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) TERHADAP KETERAMPILAN MENULIS SISWA KELAS IV SD NEGERI 17 PALEMBANG - Tia Ulfani; Darwin Effendi; Riswan Aradea (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The descriptive writing skills of fourth-grade students at SD Negeri 17 Palembang are still low because the learning process is dominated by lecture methods. This study aims to determine the effect of the STAD learning model on students' descriptive writing skills. The method used is quantitative with a quasi-experimental nonequivalent control group design. The sample consisted of 40 students divided into an experimental class (IV C) and a control class (IV A). Data were collected using an essay test. The results showed that the average posttest score of the experimental class was 82.6, higher than the control class which was 69.7. The hypothesis test using the independent sample t-test obtained t_count = 2.775 > t_table = 2.024 and sig. (2-tailed) = 0.009 < 0.05. Therefore, there is a significant effect of the STAD learning model on the descriptive writing skills of fourth-grade students at SD Negeri 17 Palembang.